IMPLEMENTASI KEBIJAKAN PENANGGULANGAN GIZI BURUK PADA BALITA DI DESA BANTERAN KECAMATAN SUMBANG TAHUN 2022 - Indriyani Choerun Nisa, Nela; Ariesta Amanda; Ariantika Sari, Lupita; Sutikno, Chamid; Ayu Permana Pribadi, Indah (Faculty of Social, Economics and Humanities, 2024)
This research is entitled “implementation of Policies for Combating Malnutrition in Toddlers in Banteran Village, Sumbang District” which aims to determine the implementation of policies for tackling malnutrition in toddlers. This research was located in Banteran Village, Sumbang District, Banyumas Regency. The method used in this research was a qualitative descriptive method which uses two sources, namely primary data and secondary data. The data collection methods used in this research were observation, interviews and documentation. The theory used in this research is the Policy Implementation theory according to George C. Edward III with four aspects, namely communication, resources, attitudes (dispositions), and bureaucratic structure with the focus of the research being the implementation of polices for dealing with malnutrition in toddlers. The implementation result obtained during the research were the implementation of the recovery supplementary feeding program (PMT Recovery) had not been running optimally, and there was an inhibiting factor in the recovery supplementary food program (PMT Recovery), namely the small amount of budget spent on purchasing additional food.